Age Difference, Not Food Scarcity or Sibling Interactions, May Drive Brood Reduction in Wild Scarlet Macaws in Southeastern Peru - Gabriela Vigo-Trauco; Gustavo Martínez-Sovero; Donald J. Brightsmith (Diversity)
Avian brood reduction was initially thought to be driven by insufficient food supply. Now it is more commonly considered a consequence of asynchronous hatching and resulting siblicide, direct filial infanticide (where parents kill specific chicks) or indirect filial infanticide (where parents starve specific chicks). In psittacines, brood reduction has been reported, but the mechanisms and causes remain unexplored. In this paper, we test the hypotheses that Scarlet Macaw chick starvation is driven by (1) sibling aggression, (2) food scarcity, and (3) parental food allocation based on (a) chick hatch weight and (b) chick age differences. We documented wild Scarlet Macaw behavior in lowland Peru in 37 nests over 19 seasons using morphological measurements and nest videos. Chick starvation was the leading cause of chick mortality (27% of all second-hatched chicks starve, and nearly all third- and fourth-hatched chicks starve). We found no evidence that starvation was caused by (1) sibling conflicts or (2) food availability. We did find parental food distribution favors first-hatched chicks, with larger age differences increasing the chances of second chick starvation. This study offers insights into brood reduction among Neotropical cavity-nesting birds and enhances our capacity to develop scientifically informed management strategies to support endangered psittacines.